Directing Clostridium ljungdahlii fermentation products via hydrogen to carbon monoxide ratio in syngas. (May 2019) - Jack, Joshua; Lo, Jonathan; Maness, Pin-Ching; Ren, Zhiyong Jason
Abstract: Clostridium ljungdahlii was grown on syngas of varying composition to investigate how syngas blends used in fermentation can be tailored toward desired product formation. Experiments were conducted with liquid batch cultures exposed to the same volume of gas with varying ratios of hydrogen to carbon monoxide (H2 /CO). Formation of acetate was favored by higher concentrations of hydrogen in the headspace. The maximum acetate concentration of 35.21 ± 0.84 mM was obtained using an H2 /CO ratio of 2.0. Generation of more reduced metabolites was favored by greater carbon monoxide concentrations in the headspace. Maximum ethanol (7.53 ± 0.58 mM) and 2, 3-Butanediol (5.20 ± 0.79 mM) concentrations were achieved under an H2 /CO ratio of 0.5. Linear relationships were obtained in that describe the effect of the syngas H2 /CO ratios on acetate, ethanol, and 2, 3-BD formation, respectively. Highlights: H2 /CO gas consumption rates are dependent on syngas blend composition. Ethanol/acetate product ratio linearly increases with added CO between H2 /CO ratios of 0.5–2.0 Total product yields and cell growth are favored by uniform syngas blends.